THE EU RESPONSE TO THE MASSIVE INFLUX OF DISPLACED PERSONS FROM UKRAINE IN 2022 - Elżbieta Hanna Morawska (Zeszyty Prawnicze)
Russia has been conducting military action against Ukraine since 24 February 2022, in violation of the prohibition on the threat or use of violence against the territorial integrity or independence of any state, which is one of the fundamental principles of modern international law.